Keberadaan Pondok Pesantren terhadap Masyarakat Sekitar - Azhar, Lazuardi Imani Poetra; Haryanto, Budi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Pesantren is a traditional Islamic educational institution that serves various functions, such as instilling religious values, fostering creativity, and playing a role in community development. Pesantren also influences the religious attitudes of the surrounding community through quality religious education and the shaping of social attitudes. This research aims to analyze the impact of the presence of Pondok Pesantren Alfattah on the religious attitudes of the surrounding community. Pondok pesantren is an Islamic educational institution with a crucial role in shaping religious and moral values in society. This study discusses Pondok Pesantren Alfattah as the object of study, located in the Buduran Subdistrict. This research employs a qualitative method with a case study approach. Data is gathered through in-depth interviews with community leaders, pesantren instructors, and several residents living around the pesantren. Additionally, participatory observation is used to understand the day-to-day activities at the pesantren and their impact on the surrounding community. The research results reveal the positive impact of the existence of Islamic boarding schools (pesantren) on the religious attitudes of the community within a radius of 0.2-2.2 kilometers from Pondok Pesantren Al-Fattah. Data collection methods involve interviews, observations, and the collection of relevant documents. Data is analyzed inductively to draw general conclusions about the pesantren's impact on the religious attitudes of the surrounding community.